Reactive power control of solar photovoltaic inverters for grid code compliance support - Muammar Zainuddin; Frengki Eka Putra Surusa; Muhammad Asri; Aprian Mokoagow (Institute of Advanced Engineering and Science, 2023)
The compensation of reactive power in smart inverters is one solution to address the issue of voltage violations in the distribution network due to the penetration of solar photovoltaic power generation. However, options for reactive power control are limited during variations in irradiation and daily load on the feeder. This study aims to investigate the performance difference between four reactive power control techniques including Q(V) control, Q(P) control, fixed Q-Var, and fixed power factor (PF) available in smart inverters to reduce voltage violations due to PV integration and comply with the grid-code. Three-phase balanced power flow was simulated in a medium voltage distribution network (MVDN) considering the reactive power control mode of the inverter under variations in solar radiation and daily load. The results showed that the Q(V) control was more effective in improving distribution feeder voltage than other techniques and showed its compliance with the grid-code. The limiting setting point for var injection or power factor limit should be proportional to the daily grid load profile.